An integrated approach to the design of thromboxane A2 receptor antagonists - Khristova, T.M.; Polishchuk, P.G.; Varnek, A.A.; Kuz’min, V. E. (Reports of the National Academy of Sciences of Ukraine, 2014)
Two approaches were used for the design of novel promising antagonists of thromboxane A2 receptors. They are based on the usage of pharmacophore models and molecular field similarity models. 223 new compounds were designed overall. Five promising antagonists of thromboxane A2 receptors were selected by earlier obtained QSAR and pharmacophore models for the further synthesis and experimental testing.